Marketing Analysis of Indonesian Sustainable Palm Oil (ISPO) and non-ISPO Certified Independent Palm Oil in Batanghari Regency, Jambi Province, Indonesia - Hutagaung, Bagasferyan; Asmarantaka, Ratna Winandi; Adhi, Andriyono Kilat (Universitas Panji Sakti, 2024)
This research analyzes marketing efficiency: marketing, marketing function, marketing margin, farmer's share, and the ratio of profit to cost of fresh fruit bunches (FFB) for ISPO (Indonesian Sustainable Palm Oil) and non-ISPO palm oil in Batanghari Regency, Jambi Province. The sample consisted of 30 ISPO farmers and 30 non-ISPO farmers, sampling farmers using a purposive method and then using the snowball sampling method to find out what institutions are involved in the ISPO and non-ISPO independent oil palm marketing process in Batanghari Regency. The research results show four marketing channels: (1) farmer-trader-large trader-palm oil weighing-mill, (2) farmer-trader-palm palm weighing-mill, (3) farmer-palm palm weighing-mill, and (4) farmer-merchant-mill. ISPO farmers do not experience differences in marketing channels and prices, which is not in accordance with the objectives of establishing ISPO. Marketing functions include purchasing, selling, transporting, harvesting, risk-bearing, financing, and market information. Analysis of marketing margin, farmer's share, and profit-to-cost ratio shows the third most efficient channel with a farmer's share of 87.82% with the farmer's marketing channel selling FFB through palm oil weighing, which distributes it to mills, involving one marketing institution.